Avaliação microbiológica de bolsas de hemocomponentes caninos do banco de sangue do Hospital Veterinário da Universidade Federal de Santa Maria - RS - Hasan, Jamile Amaral (2024)
Transfusion therapy is a fundamental therapeutic practice in veterinary medicine to treat pathologies that require replacement of blood or its components. Ensuring blood quality is essential, as any contamination can pose significant risks to the recipient patient. This study aimed to evaluate the presence of bacterial growth in blood bags collected by the HVUUFSM blood bank. Samples were collected from three groups: after bag collection, before release for transfusion and after transfusion. Still, the duration of bag collection, transfer of the first sample from the bag to the culture medium, storage time of the bag in the blood bank and duration of transfusion to the recipient were monitored. All samples were subjected to aerobic and anaerobic bacterial culture in the bacteriology laboratory. Of the 34 bags collected, 92 aliquots were obtained for blood culture. The average time for bag collection, transfer of the first sample to the culture medium, bag storage and average time for blood transfusion was, in due order: 12.7 min, 21.19 min, 3.52 days and 3h22min. The results of the blood cultures revealed a predominance of microorganisms common to the skin microbiota, such as coagulase-positive Staphylococcus (10 bags), followed by Gram-positive bacilli (9 bags), Gram-positive cocci (3 bags), Corynebacterium sp. (2 bags), Micrococcus sp. (2 bags), Gram-negative bacilli (2 bags), Enterobacteria, Bacillus sp., Enterococcus sp., Staphylococcus scheiferi, Acinetobacter sp., Gram-negative bacillus suggestive of Pasteurella sp. and Streptococcus sp. in one bag, respectively. Furthermore, 61.76% of the samples showed positive bacterial growth in at least one of the cultures, with the highest contamination rate observed in the aliquots collected after collection of the bag. These results suggest that the donor's microbial flora is the predominant source of contamination of blood bags. Therefore, the importance of rigorous antisepsis practices during donor preparation, collection, storage and infusion of blood is emphasized, aiming to mitigate contamination risks. Such processes must be standardized in order to obtain maximum quality of blood components and transfusion safety.